2019
DOI: 10.3390/genes10030219
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Patterns in the Round Goby Hypothalamus Support an On-The-Spot Decision Scenario for Territorial Behavior

Abstract: The question as to how early life experiences are stored on a molecular level and affect traits later in life is highly topical in ecology, medicine, and epigenetics. In this study, we use a fish model to investigate whether DNA methylation mediates early life experiences and predetermines a territorial male reproductive phenotype. In fish, adult reproductive phenotypes frequently depend on previous life experiences and are often associated with distinct morphological traits. DNA methylation is an epigenetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 99 publications
(146 reference statements)
0
18
0
Order By: Relevance
“…Web of Science records on round goby (orange) have risen since its first detection in the Great Lakes in contrast to records on a non-invasive fish with similar ecology (European bullhead, Cottus gobio; gray) methylating PRC2 complex and the DNA methylases. Both mechanisms are implicated in the regulation of developmental plasticity and gene expression and have been linked to plastic responses, behavioral changes, and environmental memory [51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Web of Science records on round goby (orange) have risen since its first detection in the Great Lakes in contrast to records on a non-invasive fish with similar ecology (European bullhead, Cottus gobio; gray) methylating PRC2 complex and the DNA methylases. Both mechanisms are implicated in the regulation of developmental plasticity and gene expression and have been linked to plastic responses, behavioral changes, and environmental memory [51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, results presented in this issue and elsewhere make clear that this is a time of opportunity for epigenetics as its contours and impact are traced more and more clearly: the epigenome is demonstrated to be very plastic, it changes during development [2], but also, and in a different way, when exposed to external environmental cues. These changes occur sometimes within generations [3] and, in other cases, epigenetic plasticity occurs through generations [4,5], conveying parental effects of very different type (e.g., parental diet or hatchery environment).However, this plastic character of the epigenome makes it also difficult to draw general conclusions on how every epigenotype, genotype and phenotype are interrelated. In this issue, it is shown that phenotypic, and thus potentially gene expression changes, can precede epigenetic changes [3], or that they occur after the initial environmental stimulus [4,5].…”
mentioning
confidence: 99%
“…These changes occur sometimes within generations [3] and, in other cases, epigenetic plasticity occurs through generations [4,5], conveying parental effects of very different type (e.g., parental diet or hatchery environment).However, this plastic character of the epigenome makes it also difficult to draw general conclusions on how every epigenotype, genotype and phenotype are interrelated. In this issue, it is shown that phenotypic, and thus potentially gene expression changes, can precede epigenetic changes [3], or that they occur after the initial environmental stimulus [4,5]. It is also shown that epigenetic modifications can be associated with the magnitude of change in reaction norms of some but not all phenotypic traits [6].…”
mentioning
confidence: 99%
See 2 more Smart Citations